Pelayanan Consultation Liaison Psychiatry (CLP) Menuju Peningkatan Pelayanan yang Lebih Holistik di Rumah Sakit Tingkat II Udayana Denpasar - Wirasati, Rinie Indah Chandra; Darmawan, Ede Surya (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2020)
In the past, the medical field was still dominated by a medical model approach which was still overshadowed by a physical-psychic dichotomy. The reality shows that there are a lot of 'sick' conditions that are not enough to be overcome only by a medical model approach. Many physical complaints do not show obvious physical abnormalities, as well as many physical diseases whose morbidity and mortality are strongly influenced by mental-emotional conditions. Not to mention the various conditions of chronic illness or disability, which have a mental-emotional / psychosocial impact that greatly reduces the quality of life of the patient in addition to worsening the course of the disease itself. The role of psychiatry in dealing with the psychological aspects of patients with medical conditions began to develop rapidly in developed countries after the mid-20th century and in the field of psychiatry itself it was developed in Liaison Psychiatry, but because the connection with psychiatric consultation is very strong, it is practically referred to as Consultation Liaison Psychiatry (CLP). Currently, in the JKN era, which requires hospitals to provide quality services with a Price, Product, Place and Promotion strategy, CLP services have segmenting, targeting, and positioning that are quite important to improve more holistic medical services to the community